2012
DOI: 10.1186/1742-2094-9-247
|View full text |Cite
|
Sign up to set email alerts
|

Rod microglia: elongation, alignment, and coupling to form trains across the somatosensory cortex after experimental diffuse brain injury

Abstract: BackgroundSince their discovery, the morphology of microglia has been interpreted to mirror their function, with ramified microglia constantly surveying the micro-environment and rapidly activating when changes occur. In 1899, Franz Nissl discovered what we now recognize as a distinct microglial activation state, microglial rod cells (Stäbchenzellen), which he observed adjacent to neurons. These rod-shaped microglia are typically found in human autopsy cases of paralysis of the insane, a disease of the pre-pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
204
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(230 citation statements)
references
References 42 publications
24
204
1
1
Order By: Relevance
“…Rod-shapedIba1 + cells were most evident 2 weeks post-severe TBI, which contrasts a previous report of maximal rod cells at 7 days after TBI [17]. Our model delivered a severe TBI via LFPI, while Ziebell et al [17] used a moderate midline TBI model.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Rod-shapedIba1 + cells were most evident 2 weeks post-severe TBI, which contrasts a previous report of maximal rod cells at 7 days after TBI [17]. Our model delivered a severe TBI via LFPI, while Ziebell et al [17] used a moderate midline TBI model.…”
Section: Discussioncontrasting
confidence: 50%
“…The lack of co-labeling with SMI-71 indicated that rod-shaped Iba1 + cells do not align with nearby neurovasculature (Figure 2). Ziebell et al [17] and Taylor et al [28] suggested that rod-shapedIba1 + cells align with cortical axons. Indeed, stained axons (with NF312 antibody) and dendrites (with anti-MAP2 antibody), showed an undeniable alignment with rod-shapedIba1 + cells (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased or "reactivated" astrocytes, in a process called astrocytosis, play a role in secondary injury following neurotrauma [42], and astrocytosis could be an early sign of chronic traumatic encephalopathy [27]. Serum GFAP levels predict the clinical outcome of mTBI in children [38]. Consistent with previous studies using immunochemical staining and immunoblot analysis [27,34], our real-time RT-PCR studies showed an increased expression of GFAP in the impacted compared with control brain, suggesting that secondary damage might have been underway.…”
Section: Discussionmentioning
confidence: 99%
“…This justifies our use of real-time RT-PCR to assess the reaction of the whole brain rather than the reaction of localized areas. We used two markers: IBA1 for microglia [38] and GFAP for astrocytes [39]. IBA1 is a gene that is upregulated upon the activation of microglia due to inflammation.…”
Section: Discussionmentioning
confidence: 99%